First Insights into the Biological Activity and Molecular Docking of Citral (3,7-Dimethyl-2, 6-Octadienal) Against Trichomonas vaginalis - Alexia Brauner de Mello; Juliana Montelli Fenalti; Bruna Baccega; Yan Wahast Islabão; Filipe Obelar Martins; Paloma Taborda Birmann; Angela Maria Casaril; Tallyson Nogueira Barbosa; Angela Sena-Lopes; Francieli Liz Monteiro; Lucielli Savegnago; Sibele Borsuk; et al. (Microbiology Research)
The increasing resistance of Trichomonas vaginalis to the only approved chemical family of drugs for treatment, the 5-nitroimidazoles, has prompted the exploration of new therapeutic agents against this prevalent non-viral sexually transmitted infection. Natural products have emerged as a significant source of novel treatments for trichomoniasis. The aim of this study was to evaluate the anti-T. vaginalis activity of citral (3,7-dimethyl-2,6-octadienal), the main constituent of the essential oil of Cymbopogon species, commonly known as lemongrass. Our findings indicate that citral exhibits a minimum inhibitory concentration (MIC) of 100 μM, effectively inhibiting the growth of T. vaginalis trophozoites within 12 h of exposure, and a 50% inhibitory concentration (IC50) of approximately 40 μM after 24 h. Furthermore, the evaluation of nitric oxide (NO) levels suggests that citral possesses antioxidant properties. Molecular docking studies reveal a weak interaction with three parasite proteins: thioredoxin reductase (TvTrxR), purine nucleoside phosphorylase (TvPNP), and methionine gamma lyase (TvMGL). The present study highlights the potential of citral as a candidate for the development of no-nitroimidazole drugs, offering new avenues for trichomoniasis treatment and underscoring the importance of further investigation into citral’s mechanism of action.